2019
DOI: 10.1002/jsfa.10016
|View full text |Cite
|
Sign up to set email alerts
|

Variations of peel essential oils during fruit ripening in four lemon (Citrus limon (L.) Burm. F.) cultivars

Abstract: BACKGROUND: Lemon processing procedures yield a significant amount of waste as peels, which are 57% of processed lemons and represent a possible source of bioactive compounds (essential oils, EOs). EOs were extracted from lemon fruits belonging to four cultivars harvested at four different sampling times (25 October, 23 November, 20 December, 1 February), characterized, and quantified through gas chromatography-mass spectrometry. RESULTS: The chemical composition of EOs highlighted that 26 compounds of the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
(68 reference statements)
4
22
1
Order By: Relevance
“…Some of these studies reported a limonene decrease in EO at the end of harvest time [8,23], which was not observed in this study. The decrease in the abundance of monoterpene hydrocarbons along Citrus ripening could be explained by the high unsaturation level of these compounds that would make them more unstable to factors such as light or chemical oxidation [23]. In addition, Wang and Liu (2014) reported in C. reticulata an increase of sesquiterpene hydrocarbons at the end of the harvesting period [8], although this effect was not observed in our study.…”
Section: Evolution Of the Volatile Profile Along Harvest Timecontrasting
confidence: 79%
See 2 more Smart Citations
“…Some of these studies reported a limonene decrease in EO at the end of harvest time [8,23], which was not observed in this study. The decrease in the abundance of monoterpene hydrocarbons along Citrus ripening could be explained by the high unsaturation level of these compounds that would make them more unstable to factors such as light or chemical oxidation [23]. In addition, Wang and Liu (2014) reported in C. reticulata an increase of sesquiterpene hydrocarbons at the end of the harvesting period [8], although this effect was not observed in our study.…”
Section: Evolution Of the Volatile Profile Along Harvest Timecontrasting
confidence: 79%
“…Nevertheless, no differences were detected for most compounds including limonene. The lower accumulation of several monoterpene hydrocarbons at the end of harvest time had also been reported in other Citrus EO, like C. reticulata, C. aurantium and C. limon [8,22,23]. Some of these studies reported a limonene decrease in EO at the end of harvest time [8,23], which was not observed in this study.…”
Section: Evolution Of the Volatile Profile Along Harvest Timesupporting
confidence: 67%
See 1 more Smart Citation
“…(2012), five different classes of phenolic compounds are found in Citrus species: flavanone (such as O‐dihexoside of naringenin), flavones (such as luteolin‐6‐C‐glucoside, apigenin‐7‐O‐rutinoside‐4′‐O‐glucoside, apigenin‐6‐C‐hexoside‐O‐hexoside, luteolin‐7‐O‐neohesperidoside‐4′‐O‐glucoside, and aligenin‐8‐C‐hexoside‐O‐acylrhamnoside), flavonols (such as 7‐O‐rutinosides of isorhamnetin, kaempferol, quercetin, and tamarixetin, isorhamnetin‐3‐O‐rutinoside‐7‐O‐glucoside, kaempferol‐3‐O‐rutinoside, and tamarixetin‐3‐O‐rutinoside‐7‐O‐glucoside), hydroxycinnamic acids (such as O‐hexoside of sinapic and ferulic acids), and coumarins (such as O‐rhamnosylhexoside and O‐hexoside of scopoletin). The high contents of phenolic compounds have been found in citrus species essential oils and extracts (Di Rauso Simeone et al., 2020; Hojjati & Barzegar, 2017; Sultana et al., 2015). The phenolic compounds act as electron donors in free radical reactions and are often correlated to the antioxidant effect of the essential oils.…”
Section: Resultsmentioning
confidence: 99%
“…The main CEO components are classified into terpenes (monoterpenes and sesquiterpenes), alcohols, aldehydes and esters [ 4 ]. In Citrus limon essential oils, the most abundant monoterpene hydrocarbons reported are d -limonene, γ -terpinene and β -pinene and between oxygenated monoterpenes, the most abundant are α -terpineol, nerol and geraniol [ 10 ]. Quantitatively, limonene is the main compound of C. limon essential oils at levels typically ranging between 70 and 48% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%